Capital Adequacy and Efficiency: An Empirical Study of the U.S. Banking System - Thakar, Sebastian (2014)
This paper provides an empirical analysis of the factors that determine capital adequacy of U.S. banks in the period between the years 2006 and 2012. It pays particular attention to the relationship between efficiency and capital adequacy. Efficiency results were obtained using a standard translog cost function model. Results, as expected, correlate with the recent financial crisis but do not find evidence to suggest large banks are more or less efficient than smaller ones. Following this, a GMM estimator was applied to the sample to provide main results. The GMM provided the effect of cost efficiency, along with a number of other determinants, on capital adequacy of the sample of 27 large U.S. banks. Results find that efficiency has a negative impact upon capital adequacy ratios, which would suggest that as efficiency increases, the belief that the loans given out are less likely to be ‘bad’. Furthermore, large banks tend to have lower capital adequacy buffers, which could be indicative of a ‘Too-Big-To-Fail” problem in the U.S. banking sector.